CULTIVATION OF LOGICAL INDONESIAN LANGUAGE SKILLS FOR STRENGTHENING SCIENTIFIC ACTIVITIES - Arnawa, Nengah; Liswahyuningsih, Ni Luh gede (Program Studi Pendidikan Bahasa Indonesia dan Daerah Universitas PGRI Mahadewa Indonesia, 2025)
This paper is written to build an understanding of the importance of Indonesian language skills to promote science, technology, and culture. Since November 2023, Indonesian has been designated as the official language of UNESCO. Internationally, this recognition is a great achievement. However, an ironic condition has been revealed domestically. Many students and college students are not yet skilled in Indonesian. As a result, they have difficulty in acquiring and developing science, technology, and culture. Therefore, fostering scientific Indonesian language skills is very urgent. This fostering can be done by strengthening literacy and fostering the development of critical and logical thinking skills. Nationally, strengthening literacy has been attempted through the School Literacy Movement Program (GLS); while logical thinking skills are attempted through the Pancasila Student Profile Strengthening Project (P5). Critical and logical thinking skills are an integral part of efforts to foster the use of scientific Indonesian because thinking is actually speaking internally; conversely; speaking is external thinking.